Analysis of Audio Visual Learning Media on Students' Critical Thinking Skills - Hawa Hasan; Dewa Bagus Sanjaya; I Nengah Suastika (Green Publisher Indonesia, 2025)
In meeting the challenges of the 21st century with extraordinary technological developments, educators must be able to create something new to improve students' critical thinking skills. The purpose of this study was to determine whether audio-visual learning media can improve students' critical thinking skills. The method in this research is qualitative method. The method of data collection in this study is by reviewing several journals and scientific literature or what is known as literature study. The results in this study indicate that audio visual learning media is one alternative that can be used to improve students' critical thinking skills.